2019
DOI: 10.14419/ijet.v7i4.14.27569
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cd, Cu, Ni and Pb in Selected rice Grain Available in Malaysia

Abstract: This study aims to determine the levels of heavy metals (cadmium, copper, nickel and lead) in imported and domestically produced rice grains sold in Malaysia market. A total of 10 brands of rice samples was purchased from the local market and analyzed using atomic absorption spectroscopy (AAS). Good linearity was observed over the range studied with a correlation coefficients (R2) of 0.9884-0.9999. The range values of the metals detected in rice grain samples were 0.67-0.8 mg/kg for cadmium, 2.14-7.0 mg/kg for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
4
3
Order By: Relevance
“…The Cd results found in samples were higher than the results reported by Da Silva et al[18], but lower than the results reported by Abd Rashid et al[19]. range of Cu values detected in rice grain samples reported by Abd Rashid et al[19] (2.14 -7.0 mg/kg).Zinc concentrations in black tea samples were varied between 39.3 ± 1.2 and 58.6 ± 4.5 mg/kg (Mean value equaled to 48.1 ± 9.8 mg/kg). They were similar to the results reported by Podwika et al[1] (Zn concentration in all tea samples varied from 12.6 ± 0.2 to 45.5 ± 0.1 mg/kg), results reported by Srividhya et al[16] (25.39 ± 0.59 mg/kg for black teas), reported by Rene et al[22] (21.5-75.2 mg/kg), reported by Ashraf and Mian[15] (65.7 ± 31.3 mg/kg) and reported by Srividhya et al[16] The Zn contents in tea samples ranged from 23.47 mg/kg to 52.32 mg/kg with an average value of 39.55 mg/kg were reported by Binh et al[20].…”
contrasting
confidence: 76%
See 2 more Smart Citations
“…The Cd results found in samples were higher than the results reported by Da Silva et al[18], but lower than the results reported by Abd Rashid et al[19]. range of Cu values detected in rice grain samples reported by Abd Rashid et al[19] (2.14 -7.0 mg/kg).Zinc concentrations in black tea samples were varied between 39.3 ± 1.2 and 58.6 ± 4.5 mg/kg (Mean value equaled to 48.1 ± 9.8 mg/kg). They were similar to the results reported by Podwika et al[1] (Zn concentration in all tea samples varied from 12.6 ± 0.2 to 45.5 ± 0.1 mg/kg), results reported by Srividhya et al[16] (25.39 ± 0.59 mg/kg for black teas), reported by Rene et al[22] (21.5-75.2 mg/kg), reported by Ashraf and Mian[15] (65.7 ± 31.3 mg/kg) and reported by Srividhya et al[16] The Zn contents in tea samples ranged from 23.47 mg/kg to 52.32 mg/kg with an average value of 39.55 mg/kg were reported by Binh et al[20].…”
contrasting
confidence: 76%
“…The Cd concentrations in rice samples reported by Da Silva et al[18] were changed from 11.6 to 44.9 µg/kg with an average content of 30.1 µg/kg. The range of Cd values detected in rice grain samples were 0.67 -0.8 mg/kg[19]. The Cd results found in samples were higher than the results reported by Da Silva et al[18], but lower than the results reported by Abd Rashid et al[19].…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…The Lebanese samples contained a high amount of Cd but was remarkably less than the level reported by a study conducted in Malaysia for local and imported rice (0.72 mg/kg) (Abd Rashid et al, 2019). However, in general, Cd levels in our Lebanese samples were higher than the ones reported in most studies assessing Cd content in rice.…”
Section: Cadmiumcontrasting
confidence: 75%
“…Our result for Pb contamination was higher than the level of 0.039 mg/kg reported by Voica et al (2012) (Rabbani et al, 2015). In Malaysia, Abd Rashid et al (2019) presented an even higher Pb content of 2.19 mg/kg in a small sample of Malaysian, Thai and Pakistani white rice.…”
Section: Leadmentioning
confidence: 88%